Catecholaminergic polymorphic ventricular tachycardia in adolescents: a clinical, electrocardiographic and genetic diagnosis - Rocha-Arrieta, María Concepción (2021)
Catecholaminergic polymorphic ventricular tachycardia is one of the most lethal channelopathies, characterized by ventricular arrhythmias triggered by stress or physical activity. We present the case of an adolescent who consulted for recurrent syncope precipitated by exercise. In the diagnostic approach, catecholaminergic polymorphic ventricular tachycardia was reached, with a mutation in the cardiac ryanodine receptor gene, Heterozygous c.14311G> A (p.v4771I exon 100), antiarrhythmic drugs and implantable cardioverter-defibrillator were necessary with satisfactory evolution. Clinical suspicion, stress test and genetic tests are essential for a timely diagnosis and management of this pathology.